Post-flowering biotic and abiotic stresses impact nitrogen use efficiency and seed filling in Arabidopsis thaliana. (13th January 2020) - Marmagne, Anne; Jasinski, Sophie; Fagard, Mathilde; Bill, Laurence; Guerche, Philippe; Masclaux-Daubresse, Céline; Chardon, Fabien
Abstract : Post-flowering stresses related to climate change impact N management in plants and reveal the crucial role of inflorescence stems in seed filling. Abstract: Nitrogen (N) is an essential nutrient that plants require for the synthesis of amino acids, proteins, and many other important metabolites. Plant metabolism and growth are consequently dependent on the amount of N that is assimilated and distributed from source leaves to developing sinks, such as fruits and seeds. The environmental stresses enhanced by climate change deeply influence seed yield and seed composition, and may disturb N use efficiency (NUE) in pants. We aimed to investigate plant responses to extreme climates with regard to NUE, N remobilization efficiency, and seed composition. By studying a collection of Arabidopsis genotypes showing a range of C:N ratios in seeds, we investigated the impact of different post-flowering growth conditions (control, heat, drought, low nitrate availability, induced senescence, and induced plant defense) on seed yield, N allocation in organs, NUE, and N remobilization efficiency. We analysed how post-flowering stresses could change seed filling and showed that post-flowering stresses change both the range of N and C concentrations and the C:N stoichiometry in seeds. Using a new trait, called delta seed composition, we measured the deviation in C:N stoichiometry of each genotype and revealed the genetic determinism of the C:N stoichiometry. Altogether, the results indicate that extreme climate impacts NUE dramatically in plants and generates different bottlenecks in N fluxes during seed filling.